Neural signatures of treatment-induced benefits in apathy and depression amongst persons with aphasia - López-González, Francisco Javier; Edelkraut, Lisa; Roé-Vellvé, Núria; López-Barroso, Diana; Mohr, Bettina; Pulvermüller, Friedemann; Starkstein, Sergio E.; Alfaro Rubio, Francisco; Dávila-Arias, María Guadalupe; Torres-Prioris, María José; Berthier-Torres, Marcelo Luis (My University, 2020)
Intensive language-action therapy (ILAT) reduces symptoms of depression in persons with aphasia (PWA) due to stroke. The neural correlates of such improvement remain unexplored. Here we evaluated apathy and depression in PWA receiving treatment with the cholinesterase inhibitor donepezil (DP) alone and combined with ILAT as well as the brain changes promoted by these interventions. Ten PWA with chronic left perisylvian strokes participated in a 10-week open-label pilot study. They received DP alone (wk 0-8) and thereafter combined with ILAT (wk 8-10 30 hours, wks 8-10). Structural MRI and resting state [18]fluorodeoxyglucose PET (18FDG-PET) were acquired for at 3 time-points in order to measure grey matter density (Voxel-based morphometry, VBM) and metabolic changes. The primary outcome measures were: Aphasia Quotient of the Western Aphasia Battery (AQ-WAB), Communicative Activity Log (CAL), Stroke Aphasic Depression Questionnaire (SADQ), and Stroke and Aphasia Quality of Life Scale-39 (SAQoL-39). The 21-item SADQ was used to examine apathy (7 items) and depression (14 items). Significant improvements with DP alone and under DP-ILAT were seen in AQ-WAB, CAL and SAQoL-39. Improvements in symptoms of apathy and depression were observed when comparing DP-ILAT with baseline. 18FDG-PET analysis revealed that DP alone induced significant increments in metabolic activity in cortical and subcortical areas that correlated with improvement in apathetic and depressive symptoms. VBM analyses revealed that DP alone and combined DP-ILAT induced increases in grey matter density in areas of the right hemisphere previously associated to improvements in apathy and depression. In conclusion, treatment with DP alone and combined with ILAT improved aphasia, communication and quality of life as well as associated symptoms of apathy and depression by modulating regions innervated by the left medial, right lateral and brainstem cholinergic pathways.
Keywords: Depresión mental; Treatment; Apathy; Depression; Aphasia